Doppler inspection results of first year infants with hydrocephalic syndrome of hypoxic-ischemic genesis - A. V. Kovalenko; O. V. Karkashina; K. A. Kovalkov (Бюллетень сибирской медицины)
Case monitoring of 105 infants from 1 to 12 months with 1, 2 degrees cerebral ischemia was realized. Clinical, clinical-neurovisual signs of hydrocephalic syndrome were observed in 57 patients of the first group. For 48 infants of the second group there were only neurosonographic signs of cerebrum liquor spaces dilatation. Transcranial Doppler investigation was included into case monitoring. Indices of cerebral hemodynamics determining clinical finding of intracranial hypertension were established. Principal mechanisms of cerebral hemodynamics changing under hydrocephalic syndrome for infants of the first year were found. Stable characteristics pointing to intracranial hypertension regardless of clinical finding are shown.